Model for structure formation in nanosuspension droplet superheated steam drying - Bück, Andreas (Drying Technology, 2024)
In this work, a mathematical model for particle and structure formation from drying single nanosuspension droplets in superheated steam is presented. The influence of process and material conditions on structure formation (“locking”), especially shell properties is systematically investigated by computation. It is shown that with increasing superheating, larger and more porous particles result. Formed crusts decrease in thickness but are significantly denser than the overall particle. Differences in expected particle properties compared to conventional hot air drying are evaluated, indicating the existence of an “inversion temperature”. Effects of further heat and mass transfer processes (thermal radiation, nanoparticle aggregation, nanoparticle polydispersity, and anisotropy) on structure formation are qualitatively discussed.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Droplet; drying; nanofluid; superheated vapor; suspension